Life art exploratory gallery at Petaling Jaya - Ismail, Sumarni; Lam, Xin Yee; Yusoff, Sarizal Yusman; Utaberta, Nangkula; Mohd Yunus, Mohd Yazid; Ismail, Nor Atiah (American-Eurasian Network for Scientific Information, 2015)
Conventional thinking of Malaysians makes art an abstract and complex subject to be understood. Although art is subjective and controversial to different person's perception however it can bring excitement and refresh ones' minds in everyday life. It is interesting for an urban center to gather all walk of life to interact with one and another through art intervention. Unfortunately, PJ state is a strong administrative and business hub with no entertainment centre or interesting spaces for people to discover and interact. Art is used as a strategy to revitalize abandoned or underutilised spaces. Hence, art is able to give life to these spaces and heighten the identity of the PJ State. Art appreciation can be ignited by adding art to revitalize abandoned spaces and government administrative center. The overall project aims to focus on art intervention as an underlying excitement to the rigid working routine of people, revitalize the abandoned spaces (Urban regeneration), and enhance closeness between public and government relationship (Urban revitalisation). The study is conducted using comparative case studies and physical observation on site. Comparative case studies help to analyse and set parameter of designing the entire project. On the other hand, physical observation pursues site analysis from all angle of aspects and project's potential. Findings of the study suggest a comprehensive design of an art gallery and government administrative tower through aligning public and government opinions and plans and example of successful art galleries. The significant of the paper may appear as a solution to shift the paradigm of Malaysian mindset and improving current relationship of public and MBPJ in PJ state.